Flavonoid compound icariin enhances BMP-2 induced differentiation and signalling by targeting to connective tissue growth factor (CTGF) in SAMP6 osteoblasts. - Bing Xu; Xueqiang Wang; Chengliang Wu; Lihe Zhu; Ou Chen; Xiaofeng Wang (PLoS ONE)
Background Icariin, a major active flavonoid glucoside, is widely used for the treatment of bone injury and rebuilding in the clinic because of its roles in suppressing osteoblastogenesis and promoting osteogenesis. The senescence-accelerated mouse SAMP6 was accepted as a useful murine model to reveal the mechanism of senile osteoporosis and the therapeutic mechanism of drug activity. However, little is known about the characteristics of SAMP6 osteoblasts and the associated regulatory roles of icariin. Methods We isolated and cultured osteoblasts from SAMP6 or SAMR1 mice and compared their proliferation, migration, and differentiation by performing the CCK-8 assay, cell counting assay, EdU staining, cell cycle analysis, ALP staining and activity measurement, Alizarin red staining, and RT-qPCR analysis to measure the levels of osteoblast markers, including RUNX2, Colla1 and Oc. To assess the effects of icariin on BMP-2-induced osteoblast differentiation, after BMP-2 treatment, osteoblast markers were analyzed by RT-qPCR and semi-quantitative Western blotting. The effects of icariin on connective tissue growth factor (CTGF) were measured by RT-qPCR. shRNA targeting CTGF mRNA was employed to knockdown its expression level in osteoblasts. Results The SAMP6 osteoblasts presented decreased the development and differentiation activity compared with SAMR1 osteoblasts, indicating that they are the potential mechanisms underlying age-associated disease. Moreover, SAMP6 osteoblasts presented upregulated CTGF compared with SAMR1 osteoblasts. Icariin enhanced BMP-2-induced osteoblast differentiation by downregulating CTGF expression, which tightly regulates osteoblast differentiation. By downregulating CTGF, icariin treatment upregulated phosphate-Smad1/5/8, indicating its activating effects on the BMP signaling pathway. Conclusion These results suggest that decreased osteoblast development and function potentially contributes to age-associated disease. Icariin exerts enhancing effects on BMP-2-mediated osteoblast development via downregulating CTGF.